A Pilot Study of Mindfulness Meditation for Pediatric Chronic Pain - Lynn C. Waelde; Amanda B. Feinstein; Rashmi Bhandari; Anya Griffin; Isabel A. Yoon; Brenda Golianu (MDPI AG, 2017)
Despite advances in psychological interventions for pediatric chronic pain, there has been little research examining mindfulness meditation for these conditions. This study presents data from a pilot clinical trial of a six-week manualized mindfulness meditation intervention offered to 20 adolescents aged 13-17 years. Measures of pain intensity, functional disability, depression and parent worry about their child's pain were obtained at baseline and post-treatment. Results indicated no significant changes in pain or depression, however functional disability and frequency of pain functioning complaints improved with small effect sizes. Parents' worry about child's pain significantly decreased with a large effect size. Participants rated intervention components positively and most teens suggested that the number of sessions be increased. Three case examples illustrate mindfulness meditation effects and precautions. Mindfulness meditation shows promise as a feasible and acceptable intervention for youth with chronic pain. Future research should optimize intervention components and determine treatment efficacy.